Playing with words: creativity and interaction in museums and galleries. (1st January 2016) - Patel, Menisha; Heath, Christian; Luff, Paul; vom Lehn, Dirk; Cleverly, Jason
ABSTRACT: There is growing interest within museums and galleries in enabling visitors to contribute thoughts, reflections and materials and to make these available to the wider public both within the museum space and beyond. It is widely recognised that digital technologies and developments provide unprecedented opportunities to facilitate engagement and provide new and distinctive forms of participation, sociality and creativity. In this paper, we explore how visitors responded to an installation that provided the opportunity to produce and post 'content'; content that resonated with the principal themes of the museum, and consider how the installation encouraged creativity and certain forms of sociality. In contrast to more traditional ethnographic studies of visitor behaviour, we seek to demonstrate that resources and installations designed to encourage user-generated content, demand a rather different approach to data analysis, an approach that prioritises the practices that inform the concerted production of content.